Follicular Lymphoma Presenting with Leptomeningeal Disease - Rubens Costa; Ricardo Costa; Renata Costa (Case Reports in Hematology)
Follicular lymphoma is generally an indolent B cell lymphoproliferative disorder of transformed follicular center B cells. Central nervous system metastasis is a very rare complication portending a very poor prognosis. We report a rare case of follicular lymphoma presenting with leptomeningeal involvement achieving a complete remission after initial therapy.